Gender-based violence in academic and research workplaces: Pervasiveness in higher education and research performing organisations - Strid, Sofia; Hearn, Jeff (Socialmedicinsk tidskrift, 2025)
The paper addresses gender-based violence (GBV) in higher education institutions (HEI) and research performing organisations (RPOs) understood as work, workplace, employment, occupational, organisational, professional and managerial sites. The data are based on the EU funded UniSAFE and include an online survey of prevalence and consequences of GBV (n=42,000), a mapping of national policy on GBV in higher education and RPOs, and institutional policies and measures to counteract GBV in 46 RPOs in fifteen countries. The findings show that the prevalence of GBV in RPOs is high, unequal across different groups, yet relatively uniform across countries and institutions, which suggest that the prevalence of GBV is largely unrelated to the RPOs in which respondents work or study, and/or to the country in which they reside. GBV in HEI and RPOs thus seems to have its own system and logic.